Malthus - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Land resources: on the edge of the Malthusian precipice? Edited by D J Greenland, P J Gregory and P H Nye. 1998. ISBN 0 85199 235 8.